Recombinant Human Granulocyte-Colony Stimulating Factor (rh G-CSF) in Standard Chemotherapy of Hodgkin’s Disease - Ozkalemkas, Fahir; Ali, Ridvan; Karaaslan, Yusuf; Ozkocaman, Vildan; Tunali, Ahmet (Annals of Medical Research, 2021)
None
Keywords: s : G-CSF, Hodgkin's disease, neutropenia, infection